(untitled) (Bangladesh Journal of Medical Education, 2026)
Background: With continued evolvement of modern healthcare landscape; nursing education demands the necessity of faculty development program and training to prepare students effectively. The best way to evaluate any change in learning is through assessment before and after the training. Objectives: The aim of the study was to evaluate the efficacy of a training on teaching methodology for selected teacher nurses in Chittagong division. Methods: It was a one-group pre-test post-test quasi-experimental design conducted from May 05 to May 07, 2025 at Chittagong Medical University (CMU); organized by the Faculty of Nursing, CMU in collaboration with Centre for Medical Education (CME), Bangladesh. A total of 22 teachers from 11 nursing colleges were selected for the training. Training included 12 interactive modules and 14 topics with structured content over 18 hours. A semi-structured, validated ‘multiple-choice questionnaire’ (17-points) and ‘training evaluation questionnaire’ were used as study instruments to evaluate the training. Results: There was a sharp rise in average knowledge assessment score of participants from 59.09% (pre-test) to 90.9% (post-test); which was statistically highly significant (p 0.00). The majority of participants rated all the sessions as either “Very Good” or “Excellent” or “Good” on the Likert scale. The knowledge and cooperation of trainers were mostly high rated aspects, with 81.8% of participants rating both as Excellent. The classroom environment was also rated high, with a score of 76%. Conclusion: Overall, the evaluation reflects a high level of satisfaction with the training program. Results of this pilot study might be essential for further improvement of training program, future formulation of evidence-based guidelines as well as large-scale comprehensive study in this field. BJME: Vol.-17, Issue-01, January, 2026:50-59